2013
DOI: 10.1590/s0103-84782013005000057
|View full text |Cite
|
Sign up to set email alerts
|

Teor de arsênio e adsorção competitiva arsênio/fosfato e arsênio/sulfato em solos de Minas Gerais, Brasil

Abstract: A alta toxicidade de As para homens e animais gera a necessidade de estudos do comportamento químico do arsenato nos solos que possam auxiliar na mitigação de áreas contaminadas com arsênio. Este trabalho teve por objetivo avaliar o teor total e a adsorção de As na ausência e presença dos ânions fosfato e sulfato em seis diferentes classes de solos do estado de Minas Gerais, Brasil. Os solos alvo deste estudo são: o Neossolo Flúvico (RU), Gleissolo Háplico (GX), Gleissolo Melânico (GM), Latossolo Vermelho Dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
4
0
3
Order By: Relevance
“…In another study, Campos et al (2013a) observed levels of As ranging between 0.14 mg kg −1 (for a gley soil) and 9.3 mg kg −1 (for an oxisol) in soils from Minas Gerais. Those concentrations are usually found in non-contaminated soils (b10 mg kg −1 ) (Adriano, 2001;Campos et al, 2007Campos et al, , 2013aBundschuh et al, 2012) and are similar to the ones reported in the present study.…”
Section: Total As Concentration In Soilsupporting
confidence: 91%
See 3 more Smart Citations
“…In another study, Campos et al (2013a) observed levels of As ranging between 0.14 mg kg −1 (for a gley soil) and 9.3 mg kg −1 (for an oxisol) in soils from Minas Gerais. Those concentrations are usually found in non-contaminated soils (b10 mg kg −1 ) (Adriano, 2001;Campos et al, 2007Campos et al, , 2013aBundschuh et al, 2012) and are similar to the ones reported in the present study.…”
Section: Total As Concentration In Soilsupporting
confidence: 91%
“…The observed behavior of soluble and available As in these soils may be partly explained by their interactions with available P (Table 2), which showed positive correlation with both fractions in all the three layers studied (Table 3). This is expected as a greater content of P in oxidic soils (which retain phosphate strongly) make As much more available and soluble due to competitive adsorption on positively-charged sites (Campos et al, 2013a).…”
Section: Extractable Soil As (Soluble and Available)mentioning
confidence: 99%
See 2 more Smart Citations
“…Trabalhos realizados com solos desenvolvidos sob condições tropicais úmidas (ambiente reconhecido pelos baixos teores de material amorfo na fração argila, normalmente inferiores a 5%) Melo et al (2002) 2-, o alto valor do coeficiente de correlação entre o teor de material amorfo e CMAAs (r = 0,88* -Tabela 5) é indicativo do possível efeito combinado da elevada área superficial específica desses minerais aliado a adsorção específica, que independe do sinal da carga de superfície. Como ocorre para o P (GEELHOED; HIEMSTRA; VAN RIEMSDIJK, 1997), íons arsenato apresentam forte afinidade por grupos hidroxilados da superfície dos minerais, o que favorece a troca de ligantes (HAsO 4 2-por OH -ou OH 2 + ) e a adsorção específica (esfera interna ou quimiossorção) do composto (CAMPOS et al, 2013). Mesmo que quantitativamente seja menos expressiva que a adsorção não específica, a quimiossorção é de extrema importância em termos ambientais por se tratar de ligação mais forte e estável entre ligante e coloide do solo (MCBRIDE, 1989;ZANGH;SELIM, 2005).…”
Section: Resultsunclassified